2001
DOI: 10.1046/j.1537-2995.2001.41030419.x
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism, GVHD, and tolerance in solid organ transplantation

Abstract: The phenomenon of microchimerism and its relationship to long-term graft tolerance is an area of active study. The ability to establish a tolerant state has been enhanced with current immunosuppressive drugs and emerging therapies such as donor HPC infusions. An undesirable outcome of host-donor WBC interaction is GVHD. GVHD is a rare complication reported most frequently in liver transplantation. Two cases of GVHD reported in recipients of organs from donors homozygous for a shared HLA haplotype would support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 62 publications
0
63
0
1
Order By: Relevance
“…HLA-typing, STR, cytogenetic and FICTION analyses proved this leukemia to be donor-derived. 2 To our knowledge, this is the first report demonstrating allograft-localized donor-derived leukemia.…”
mentioning
confidence: 75%
“…HLA-typing, STR, cytogenetic and FICTION analyses proved this leukemia to be donor-derived. 2 To our knowledge, this is the first report demonstrating allograft-localized donor-derived leukemia.…”
mentioning
confidence: 75%
“…More than 30 years ago it was recognized that transplanted organs (allografts) in human recipients become genetic chimeras. 34,42 In 1992, Starzl and colleagues 31 showed that not only is the donor organ populated by host recipient cells, but that the host recipient organs became populated by donor cells. This mutual crosspopulation of transplanted donor cells and recipient organs was termed microchimerism.…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that the mixed chimeric state results from a two-way interaction between donor and recipient leukocytes vying for dominance, similar to a two-way mixed lymphocyte reaction. 31,34 The balance between the recipient immune system and the donor leukocytes that determines whether the outcome is graft rejection (recipient leukocytes dominate), graft versus host disease (donor leukocytes dominate), or a mutually acceptable tolerant state develops between the transplant and host acceptance. It has been suggested that the donor-tolerizing dendritic cells must originate from a population of stem cells present in the donor organ to explain the existence of foreign tissue tolerance by the host for 30 years or more.…”
Section: Discussionmentioning
confidence: 99%
“…37 From an evidence-based standpoint, there is even 1 study that suggested recipients of solid organ kidney transplant had superior outcomes when they received nonirradiated blood components. 38 It should be noted that there have not been any reported cases of TA-GVHD in humoral immunodeficiency syndromes or in conditions with primary neutrophil dysfunction, so these patients do not require irradiated blood products.…”
Section: 36mentioning
confidence: 99%